Conceptual Model of Informal Business Development Based on Intellectual Capital - Sumual, Tinneke Evie Meggy; Arham, Muhammad Amir; Kawulur, Arie; Rimbing, Rocky (AIBPM Publisher, 2021)
This paper aims to describe the conceptual model of informal business development applied to â€œTibo-Tiboâ€ fisherwomen in North Minahasa Regency. Data and information were obtained by observation and structured interviews to â€œTibo-Tiboâ€ fisherwomen, business partners and village governments. The data was analyzed qualitatively by using Miles Huberman perspective, through stages: data reduction, data presentation, conclusion drawing and verification. After going through the validity of experts, this paper produced a conceptual model of informal business development based on intellectual capital namely human capital, social capital and organizational capital. This paper recommends that through the intellectual capital approach